Influence of Mg and Si content on infrared radiation performance of AP/HTPB system in each band. Issue 1 (January 2021) - Shi, Chengkuan; Ju, Jian; Li, Zejun; Guo, Zefeng; Guan, Hua
Abstract: The limited effort in this paper is focused on studying the effects of different contents of high-energy additives on infrared radiation performance of AP/HTPB systems in each band. A Spectraline SC7000 imaging spectrometer was used to test the radiation performance of each band. The test results show that when the magnesium (Mg) content increases from 0 to 30%, the near-infrared radiation intensity is greatly increased. The near-infrared radiation energy increases from 19 to 125W/Sr by 558%, the mid-infrared radiation energy increases from 32 to 85W/Sr by 166%, and the far-infrared radiation energy increased from 9.4 to 12.8W/Sr by 36%.The ratio of θα/β/λ changed from 0.59:1:029 to 1.47:1:0.15. The increase of silicon (Si) content from 0 to 30% has a great contribution to the increase of the radiation intensity in the far-infrared band. The intensity of near-infrared radiation increased from 19 to 97W/Sr by 411 %, the energy of mid-infrared radiation increased from 32 to 64W/Sr by 82%, and the energy of far- infrared radiation increased from 9.4 to 40W/Sr by 326%. The ratio of θα/β/λ has changed from 0.59:1:0.29 to 1.52:1:0.63.